The Landscape of Persistent Viral Genomes in ART Treated SIV, SHIV, and HIV-2 Infections - Bender, Alexandra M. (Cell Host Microbe, 2019)
Evaluation of HIV cure strategies is complicated by defective proviruses that persist in ART treated patients but are irrelevant to cure. Nonhuman primates (NHP) are essential for testing cure strategies. However, the persisting proviral landscape in ART treated NHPs is uncharacterized. Here we describe viral genomes persisting in ART treated, simian immunodeficiency virus (SIV) infected NHPs, simian-human immunodeficiency virus (SHIV) infected NHPs, and humans infected with HIV-2, an SIV-related virus. The landscapes of persisting SIV, SHIV, and HIV-2 genomes are also dominated by defective sequences. However, there was a significantly higher fraction of intact SIV proviral genomes compared to ART treated HIV-1 or HIV-2 infected humans. Compared to humans with HIV-1, SIV-infected NHPs had more hypermutated genomes, a relative paucity of clonal SIV sequences, and a lower frequency of deleted genomes. Finally, we report an assay for measuring intact SIV genomes which may have value in cure research.